Measurements of direct CP asymmetries in B → Xsγ decays using sum of exclusive decays - Lees, Jean-Pierre; Poireau, V.; Tisserand, V.; Grauges, E.; Palano, A.; Eigen, G.; Stugu, B.; Brown, D. N.; Kerth, L. T.; Kolomensky, Yu. G.; Lee, M. J.; Lynch, G.; et al. (Physical review. D, Particles, fields, gravitation, and cosmology, 2014)
We measure the direct CP violation asymmetry, ACP, in B→Xsγ and the isospin difference of the asymmetry, ΔACP, using 429 fb−1 of data collected at Υ(4S) resonance with the BABAR detector at the PEP-II asymmetric-energy e+e− storage rings operating at the SLAC National Accelerator Laboratory. B mesons are reconstructed from ten charged B final states and six neutral B final states. We find ACP=+(1.7±1.9±1.0)%, which is in agreement with the Standard Model prediction and provides an improvement on the world average. Moreover, we report the first measurement of the difference between ACP for charged and neutral decay modes, ΔACP=+(5.0±3.9±1.5)%. Using the value of ΔACP, we also provide 68% and 90% confidence intervals on the imaginary part of the ratio of the Wilson coefficients corresponding to the chromomagnetic dipole and the electromagnetic dipole transitions.
Gesehen am 13.04.2021
Im Titel ist der Buchstabe "s" tiefgestellt